The Little Data Book on Gender in Africa 2012/13 - World Bank (Washington, DC, 2013)
The Little Data Book on Gender in Africa 2012/13 provides a summary collection of gender statistics on Africa available in one volume. It contains 60 indicators, covering 53 African countries. Additional data may be found on the companion CD-ROM or online, covering about 1,700 indicators from 1961 to 2011. Key themes are : • Basic demographic indicators • Education • Health • Labor force and wages • Women’s empowerment. Designed to provide all those interested in Africa with quick reference and a reliable set of data to monitor development programs and aid flows in the region, this is an invaluable pocket edition reference tool for analysts and policy makers who want a better understanding of the economic and social developments occurring in Africa. For free access to Africa Development Indicators online, please visit http://data.worldbank.org/data-catalog.